Gender differences in air movement preference after moderate-intensity exercise - Shiwu Zhang; Shengkai Zhao; Zhen Sun; Yongchao Zhai (Frontiers of Architectural Research)
This study investigates the air movement preference of males and females after moderate-intensity exercise. 35 participants dressed in 0.6 clo exercised for 15 min in a room at 30 °C and then entered another room at 24 °C/26 °C/28 °C. During the experiment, participants were able to adjust the fan speed according to their own thermal comfort needs. The results indicate that after a change in metabolic rate, female prefer higher fan usage and greater air movement compared to males. When the body returns to thermal comfort, male have higher fan usage and prefer higher air movement than female. There were no difference in subjective evaluation and skin temperature between female and male. However, the skin evaporative heat loss of female was significantly lower than that of male. The correlation between air temperature, air speed and the time after entering the room tailored to the thermal requirements of distinct genders following moderate-intensity exercise has been established, which can provide a comprehensive control strategy for achieving both comfortable and energy-efficient thermal environments.